COMMUNITIES PARTICIPATORY LEVEL ON PEATLAND RESTORATION ACTIVITIES IN PAMPANGAN, SOUTH SUMATERA, INDONESIA - Rosana, Elly; Lubis, Djuara; Muljono, Pudji; Fatchiya, Anna (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
The revitalization of livelihood sources basically is empowering the local community as part of functional peatland ecosystem restoration. Pampangan district was situated in peatland ecosystem and for generations the communities have been survived and habituated with particular life skill on agriculture, livestock and fish production. As part of the peatland restoration program; a group of local inhabitants of Pampangan district (Bangsal village) participated in an economic revitalization program. The research aimed to investigate the participation level of the resident group in the economic revitalization program. Survey method with saturated sampling technique were applied to 15 member of Ulak Kuto Mandiri group. informan included all buffalo farmers who had participated in the economic revitalization initiative. This research uses primary data and secondary data. Primary data is data obtained directly from informants through interviews, observations and filling out questionnaires. and the data were processed with likert scale then descriptively explained following tabulation. The result showed that the participatory level of the economic revitalization program in Bangsal village was categorized as high which attributed to the synchronization of participants particular life skill with the economic revitalization program itself. This finding reflected the necessity to synchronize the peatland revitalization program with the peatland livelihood.